TURN-TAKING STRATEGIES IN THE SECOND AMERICA’S PRESIDENTIAL DEBATE 2020: DISCOURSE ANALYSIS - Ramdhany, Nadha Jelang; Ambalegin, Ambalegin (Asosiasi dosen IDEBAHASA KEPRI, 2025)
Turn-taking is a way that can be referred to as the change of position when the speaker becomes the listener and vice versa in the conversation. This research aims to identify the turn-taking strategies utilized by the debate participants in the second America’s presidential debate 2020. The researchers adhered to the theory of Stenström regarding turn-taking strategies. The research design was qualitative. The observational method and note-taking technique were employed to collect the research data. The analytical technique of discourse analysis and coding were performed to analyze the data. The results of this research were displayed descriptively in the form of words to sentences. The turn-taking strategies were taking the turn, holding the turn, and yielding the turn. The results revealed that the taking the turn strategy was frequently utilized by all of the participants in the debate. The interrupting strategy was commonly used by Donald Trump. Joe Biden with starting up strategy. Kristen Welker tended to perform a prompting strategy. Moreover, the silent pauses as the sub-strategy of holding the turn, appealing, and giving up as part of yielding the turn strategy were not found in the data source. The participants tended to avoid silent pauses and tried to take the floor to speak in order to show their dominance. The nature of the turn-taking system is in line with the existence of power between participants’ relationships.